Bayesian adaptive design for clinical trials in Duchenne muscular dystrophy. (7th May 2021) - Lake, Stephen L.; Quintana, Melanie A.; Broglio, Kristine; Panagoulias, Jennifer; Berry, Scott M.; Panzara, Michael A.
Abstract : A Bayesian adaptive design is proposed for a clinical trial in Duchenne muscular dystrophy. The trial was designed to demonstrate treatment efficacy on an ambulatory‐based clinical endpoint and to identify early success on a biomarker (dystrophin protein levels) that can serve as a basis for accelerated approval in the United States. The trial incorporates placebo augmentation using placebo data from past clinical trials. A thorough simulation study was conducted to understand the operating characteristics of the trial. This trial design was selected for the US FDA Complex Innovative Trial Design Pilot Meeting Program and the experience in that program is summarized.